2015
DOI: 10.1089/nat.2014.0527
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Splicing by Single-Stranded Silencing RNAs

Abstract: Single-stranded silencing RNAs (ss-siRNAs) are chemically modified single-stranded oligonucleotides that can function through the cellular RNA interference (RNAi) machinery to modulate gene expression. Because their invention is recent, few studies have appeared describing their use and the potential of ss-siRNAs as a platform for controlling gene expression remains largely unknown. Using oligonucleotides to modulate splicing is an important area for therapeutic development and we tested the hypothesis that ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In this study we focused on AGO2 because it is (i) a central factor for RNAi activity Rand et al 2004; Joshua-Tor and Hannon 2011); (ii) present in mammalian cell nuclei (Robb et al 2005;Ohrt et al 2012;Gagnon et al 2014a); and (iii) can modulate RNA-mediated control of transcription (Janowski et al 2005;Li et al 2006;Chu et al 2010;Huang et al 2010;Matsui et al 2013) and splicing (Liu et al 2012(Liu et al , 2015. RNA sequencing (RNA-seq) of nuclear RNAs that interact with AGO2 has revealed read clusters near intronexon junctions and at gene promoters (Chu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we focused on AGO2 because it is (i) a central factor for RNAi activity Rand et al 2004; Joshua-Tor and Hannon 2011); (ii) present in mammalian cell nuclei (Robb et al 2005;Ohrt et al 2012;Gagnon et al 2014a); and (iii) can modulate RNA-mediated control of transcription (Janowski et al 2005;Li et al 2006;Chu et al 2010;Huang et al 2010;Matsui et al 2013) and splicing (Liu et al 2012(Liu et al , 2015. RNA sequencing (RNA-seq) of nuclear RNAs that interact with AGO2 has revealed read clusters near intronexon junctions and at gene promoters (Chu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…AGO2 can act in conjunction with guide RNAs to regulate transcription (Chu et al 2010;Matsui et al 2013) and splicing (AmeyarZazoua et al 2012;Liu et al 2015) in human cells. While RNAi can be active in cell nuclei, there are also significant differences.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the two studies are in agreement in proposing an antisense transcript, rather than pre-mRNA, as RISC-mediated splicing control target. In contrast, Liu et al [77,79] have suggested that both duplexes, RNA molecules and single stranded RNAs complementary to sequences near exon/intron junctions, may modulate splicing by leading AGO2 to pre-mRNAs. These small oligonucleotides would induce exon skipping in a chromatin modification independent manner.…”
Section: Mirnas: Nuclear Functionsmentioning
confidence: 99%
“…As 60% of point mutations associated with diseases have been found to be related to splicing defects (Jensen et al, 2009), several methods have been developed to modify alternative splicing. For example, duplex RNAs have also been used to modify alternative splicing in mammalian cells (Liu et al, 2012), and a method of using single stranded siRNAs has been developed to modify the splicing of a Dystrophin RNA, which is associated with Duchene muscular dystrophy (Liu et al, 2015). The results of our work introduce the possibility of microRNAs as tools to modulating alternative splicing.…”
Section: Microrna Mir-1002 Is a Part Of The Stress Response Networkmentioning
confidence: 92%